Genome-Wide Gene by Environment Interaction Analysis Identifies Common SNPs at 17q21.2 that Are Associated with Increased Body Mass Index Only among Asthmatics. - Leyao Wang; William Murk; Andrew T DeWan (PLoS ONE)
Asthmatics have an increased risk of being overweight/obese. Although the underlying mechanisms of this are unclear, genetic factors are believed to play an essential role. To identify common genetic variants that are associated with asthma-related BMI increase, we performed a genome-wide gene by environment (asthma) interaction analysis for the outcome of BMI in the Multi-Ethnic Study of Atherosclerosis (MESA) study (N = 2474 Caucasians, 257 asthmatics), and replicated findings in the Framingham Heart Study (FHS) offspring cohort (N = 1408 Caucasians, 382 asthmatics). The replicable tagging SNP, rs2107212, was further examined in stratified analyses. Seven SNPs clustered in 17q21.2 were identified to be associated with higher BMI among asthmatics (interaction p < 5×10-7 in MESA and p < 0.05 in FHS). In both MESA and FHS asthmatics, subjects carrying the A allele on rs2107212 had significantly higher odds of obesity than non-carriers, which was not the case for non-asthmatics. We further examined BMI change subsequent to asthma diagnosis over a period of 26 years in FHS and demonstrated greater BMI increase among asthmatics compared to non-asthmatics. Asthmatics carrying the A allele at rs2107212 had significantly greater net BMI increase over the 26-year period compared to non-asthmatics. In this study, we found that common genetic variants on 17q21.2 are associated with post-asthma BMI increase among Caucasians. This finding will help elucidate pathways involved in the comorbidity of asthma and obesity.